Integrative metabolomics and proteomics reveal the effects and mechanisms of Salvia miltiorrhiza in alleviating traumatic blood stasis syndrome - Guo, Pei; Wang, Xin; Chen, Qi; Dong, Xufeng; Qin, Zhihua; Liu, Jiaguo (Frontiers in Veterinary Science, 2025)
Salvia miltiorrhiza (SM) is widely used in clinical practice for the treatment of cardiovascular diseases. However, the efficacy and mechanisms of SM in addressing traumatic blood stasis syndrome (TBSS) have not been thoroughly investigated. We established a TBSS model in cats and examined the muscle swelling rate (MSR), pain index, coagulation index, hematological parameters, inflammatory factors, and platelet function levels to assess the effects of SM. Subsequently, integrative metabolomics and proteomics were employed to elucidate the effects and mechanisms of SM in alleviating TBSS. The results demonstrate that the effect of SM was evaluated by establishing a cat model of TBSS. Administration of SM for 10 days significant decrease in markers such as MSR, pain index, WBC, PLT, PCT, FIB, PAI-1, TNF-α, IL-6, IL-1β, TXB2, TXB2/6-Keto-PGF1α, β-TG, and PF4. Additionally, there was a significant increase in APTT, PT, TT, t-PA, IL-10, 6-Keto-PGF1α, and FN. These findings suggest that SM regulates swelling and pain, inflammatory responses, coagulation and fibrinolytic system abnormalities, as well as platelet aggregation and activation. Through platelet metabolomic and proteomic analyses, it was found that SM inhibited the aggregation and activation processes of TBSS platelets by modulating physiological pathways, including tryptophan metabolism, purine metabolism, fatty acid metabolism, the complement and coagulation cascades, and platelet activation.